Efficient fixation of carbon dioxide by electrolysis - Facile synthesis of useful carboxylic acids - Tokuda, Masao (2006)
Electrochemical fixation of an atmospheric pressure of carbon dioxide to organic compounds is a useful and attractive method for a synthesis of various carboxylic acids. Electrochemical fixation of carbon dioxide, electrochemical carboxylation, to organic halides, organic triflates, alkenes, aromatic compounds and carbonyl compounds can readily take place in the presence of an atmospheric pressure of carbon dioxide to give the corresponding carboxylic acids in high yields when a sacrificial anode such as magnesium or aluminum is used in the electrolysis. The electrochemical carboxylation of vinyl bromides was successfully applied to a synthesis of the precursor of non-steroidal anti-inflammatory agents such as ibuprofen and naproxen. On the other hand, supercritical carbon dioxide (scCO2) has significant potential as an environmentally benign solvent in organic synthesis and it could be used both as a solvent and a reagent in these electrochemical carboxylations by using a small amount of co-solvent.